2021
DOI: 10.1038/s41398-020-01082-z
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic processes and immune-related pathways implicated in Tourette syndrome

Abstract: Tourette syndrome (TS) is a neuropsychiatric disorder of complex genetic architecture involving multiple interacting genes. Here, we sought to elucidate the pathways that underlie the neurobiology of the disorder through genome-wide analysis. We analyzed genome-wide genotypic data of 3581 individuals with TS and 7682 ancestry-matched controls and investigated associations of TS with sets of genes that are expressed in particular cell types and operate in specific neuronal and glial functions. We employed a sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 82 publications
2
29
0
Order By: Relevance
“…Finally, studies investigating other immune-related genes have revealed specific associations. For example, within CARD8 (caspase recruitment domain 8, a gene involved in caspase function), the rs2053211 single nucleotide polymorphism was not found to be involved in GTS [63], whereas NCR1 (natural cytotoxicity triggering receptor 1) and GZMB (encoding granzyme B) were more highly expressed in GTS patients than in control subjects [64,65].…”
Section: Is There Immunog Ene Tic Control Of G Ts?mentioning
confidence: 99%
“…Finally, studies investigating other immune-related genes have revealed specific associations. For example, within CARD8 (caspase recruitment domain 8, a gene involved in caspase function), the rs2053211 single nucleotide polymorphism was not found to be involved in GTS [63], whereas NCR1 (natural cytotoxicity triggering receptor 1) and GZMB (encoding granzyme B) were more highly expressed in GTS patients than in control subjects [64,65].…”
Section: Is There Immunog Ene Tic Control Of G Ts?mentioning
confidence: 99%
“…rs2504235 is in strong linkage disequilibrium with the common FLT3 missense variant rs1933437 (p.Thr227Met), which in the same study had a p-value of 8.2 × 10 −8 [78]. This latter variant drove the association between GTS and a lymphocytic gene set in a recent large pathway analysis based on genome-wide genotypic data from 3581 GTS individuals and 7682 controls [105]. The association between lymphocytic genes, FLT3, and GTS not only provides further support for a role of FLT3 in GTS, but also suggests an involvement of a neuroinflammatory element in disease pathogenesis.…”
Section: Flt3mentioning
confidence: 81%
“…Due to the fall in the running costs, exome and genome sequencing are now attractive alternative methods for detecting novel and rare variants, and exome sequencing in particular has been utilized in several recent GTS studies [100,101,104,116,117]. Through pathway analyses, Tsetsos et al identified three significant gene sets that may be involved in GTS pathogenesis, demonstrating yet another useful approach in the search for candidate GTS susceptibility genes [105]. Meta-analyses and replication studies of the most significant hits from all of these screening studies, in combination with functional analyses such as investigation of mRNA expression, methylation patterns or the more cumbersome cellular studies, would be future approaches for a better understanding of the underlying genetic risk factors in GTS.…”
Section: Discussion-future Opportunities and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…That study also identified shared genetic variance with OCD and autism spectrum disorder. The Brainstorm Consortium Genome-wide association study data on 3581 patients with TS and 7682 controls identified three significant gene sets involving ligand-gated ion channel signaling, lymphocytic and cell adhesion, and trans-synaptic signaling processes 72 .…”
Section: Etiologymentioning
confidence: 99%